Application of the 2017 McDonald diagnostic criteria for multiple sclerosis in Korean patients with clinically isolated syndrome. (October 2019) - Hyun, Jae-Won; Kim, Woojun; Huh, So-Young; Park, Min Su; Ahn, Suk-Won; Cho, Joong-Yang; Kim, Byung-Jo; Lee, Sang-Hyun; Kim, Su-Hyun; Kim, Ho Jin
Objectives: To evaluate the validity of the revised 2017 McDonald criteria for multiple sclerosis (MS) compared with the 2010 McDonald criteria to predict conversion to clinically definite multiple sclerosis (CDMS) in patients with clinically isolated syndrome (CIS). Methods: A total of 163 patients from seven referral hospitals in Korea, who experienced a first clinical event suggestive of MS between 2006 and 2017, were enrolled. Patients were stratified into two groups according to outcome at the last visit: CDMS converters who experienced a second clinical event and non-converters. Results: Of the 163 patients with a mean follow-up of 63 months, 60% converted to CDMS. The sensitivity, specificity, positive and negative predictive values and accuracy were, respectively, 88.8%, 43.1%, 70.2%, 71.8% and 70.6% for the 2017 McDonald criteria and 53.1%, 69.2%, 72.2%, 49.5% and 59.5% for the 2010 McDonald criteria. After exclusion of 82 patients who received disease-modifying agents before the second attack, the specificity of the 2017 and 2010 McDonald criteria increased to 85.0% and 95.0%, but sensitivity decreased to 83.6% and 47.5%, respectively. Conclusion: The 2017 McDonald criteria afforded higher sensitivity and accuracy but lower specificity compared with the 2010 McDonald criteria for prediction of conversion to CDMS in Korean CIS patients.